Analisis Perencanaan Manajemen Risiko Bisnis di Human Resource and General Affairs pada Perguruan Tinggi - Siti Rohani; Wisnu Yuwono (Jurnal Bangkit Indonesia, 2023)
The rapid growth rate of universities has led to high competition between universities. Risk management is very necessary to be carried out in Higher Education because it can effectively assist Higher Education in achieving the goals that have been set. The purpose of this research is to analyze the risk management planning that exists in the Bureau of General Administration and Personnel. This research includes several aspects that will be analyzed, namely risk register, risk event and trigger, risk breakdown structure (RBS), risk response, and risk analysis. This research uses qualitative research methods, namely by analyzing risks in accordance with the conditions that occur in the workplace which have been adjusted to the stages of the management process in the ISO 31000: 2018 framework on Risk Management Standards. The object of this research is the Bureau of General Administration and Personnel. This research was researched using observation, literature study and document study methods. The results showed that at the Bureau of General Administration and Personnel there are 5 (five) risks analyzed, each of which has a trigger, impact, internal factors and external factors, response in handling risks, and analysis level for each risk. Recommendations for future research are that researchers can develop a broader research model and work division. The scope of risks analyzed can also be added again.